Underwater Corrosive Material Identification and Image Enhancement - Keerthana, N V; Srija, V; Poornima Devi, R; Roopini, B; Sharumathi, J M (2025 International Conference on Visual Analytics and Data Visualization (ICVADV), 2025)
One of the most essential problems underwater during the transmission of gas or crude oil through carbon steel pipelines is corroded, it is the critical issue-the subject of numerous research employing a variety of methodologies. The main goal of this research is to create a reliable and competent model that can precisely detect corrosion using certain algorithms specifically underwater image enhancement for corrosion pipeline inspection to improve the input photos, a dependable algorithm is used. The findings of this detection model show that the underwater image enhancement for corrosion pipeline inspection could be easily identified using a resized image and edge detection.